2000
DOI: 10.1152/ajpendo.2000.278.6.e1067
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and subcellular distribution of MCT1 and MCT4 in heart and fast-twitch skeletal muscles

Abstract: The expression of two monocarboxylate transporters (MCTs) was examined in muscle and heart. MCT1 and MCT4 proteins are coexpressed in rat skeletal muscles, but only MCT1 is expressed in rat hearts. Among six rat fast-twitch muscles (red and white gastrocnemius, plantaris, extensor digitorum longus, red and white tibialis anterior) there was an inverse relationship between MCT1 and MCT4 (r = -0.94). MCT1 protein was correlated with MCT1 mRNA (r = 0.94). There was no relationship between MCT4 mRNA and MCT4 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
127
0
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(154 citation statements)
references
References 35 publications
16
127
0
11
Order By: Relevance
“…The GLUT-4 was detected with a commercially available antibody (East Acres Biologicals). The monocarboxylate transporter MCT4 was detected by using an antibody prepared in our laboratory (7).…”
Section: Methodsmentioning
confidence: 99%
“…The GLUT-4 was detected with a commercially available antibody (East Acres Biologicals). The monocarboxylate transporter MCT4 was detected by using an antibody prepared in our laboratory (7).…”
Section: Methodsmentioning
confidence: 99%
“…FAT/CD36 and FABPpm protein content was determined in both homogenates and giant sarcolemmal vesicles prepared from heart, skeletal muscle, adipose tissue, and liver ( Fig. 1), as we have described previously (6,8,9,11,29). For detection of FAT/CD36 and FABPpm, we used MO-25 (30) and a rabbit polyclonal anti-FABPpm antiserum (13), respectively.…”
Section: Northern and Western Blottingmentioning
confidence: 98%
“…While MCT1 is generally localised to the plasma membrane (Philp et al 1998, 2003a, 2003b, Bergersen et al 1999, Fanelli et al 2003, Clamp et al 2004, tissue fractionation has revealed MCT1 in sarcoplasmic reticulum, T-tubules, triads, and intracellular membranes of rat heart and skeletal muscle (Bonen et al 2000) and in rat liver peroxisomes (McClelland et al 2003). These data are consistent with our finding that MCT1 immunoreactivity, while it appears brighter in the cytoplasmic cortex of cleavage-stage embryos, persists diffusely in the cytoplasm of morulae and early blastocysts.…”
Section: Effect Of Glucose On Mct Expression In Vitromentioning
confidence: 99%